Handling Time Series Data: Capabilities & Performance in Snowflake and Databricks - Rameshbabu Lakshmanasamy (North American Journal of Engineering Research, 2024)
Time series data is a set of data points arranged chronologically in a sequence and captured at regular intervals. The high levelof variability plays an essential role in a wide range of domains, including finance (stock quotes and trading volumes), IoTdevices (sensor data, machinery analytics), and weather forecasting. It allows organizations to observe patterns and trends anddraw conclusions over time. Working with time series data involves proper storage and processing of data together with fastor near-real-time analysis capability